Remarkable mechanofluorochromism and low efficiency-off electroluminescence from a fully aromatic D-A cruciform emitter. (April 2020) - Xu, Xin; Xu, Lei; Sun, Qikun; Yue, Lingtai; Wang, Yaguang; Yu, Guangshui; Zhang, Haichang; Xue, Shanfeng; Yang, Wenjun
Abstract: Two-dimensional aryl center-crossed cruciforms generally exhibit the strongly twisted conformation and the spatial separation of frontier molecular orbitals, which can render the emitters destructible packing structures and high solid-state fluorescence efficiency. In the current work, we design and synthesize a benzene-centered cruciform emitter (DOT) with two adjacent phenyloxadiazoles and two adjacent triphenylamines starting from commercially available chemicals. Single crystal analysis indicates that DOT molecules loosely pack together in a twisted conformation and weak inter-molecular interactions. Upon mechanical grinding, the crystalline DOT is changed into an amorphous state, accompanying with a remarkable (56 nm) mechanofluorochromism (MFC). In view of the crossed donor and acceptor structure and the strong solid-state fluorescence, the non-doped electroluminescence (EL) devices with the structures ITO/HATCN/NPB or TAPC/DOT/TPBi/LiF/Al are fabricated. The devices efficiently emit 500 nm green EL with the low turn on voltage of 2.7 V and the low efficiency roll-off. Thus, we have provided a feasible synthetic strategy for various isomers and analogues of fully aromatic benzene-centered D‒A cruciforms and demonstrated a new class of candidates for MFC and EL materials. Graphical abstract: Image 1 Highlights: A new two-dimensional conjugated molecule is designed and synthesized. Crossed donor-acceptor molecules show high light-emitting efficiency. Cruciforms with strong twisted structure are easy to mechanofluorochromismȦ non-doped EL device with low efficiency off is achieved.